The Hepatitis E Virus Open Reading Frame 2 Protein: Beyond Viral Capsid - Zhou, Zhaobin; Xie, Yinqian; Wu, Chunyan; Nan, Yuchen (Frontiers in Microbiology, 2021)
Hepatitis E virus (HEV) is a zoonotic pathogen causing hepatitis in both human and animal hosts, which is responsible for acute hepatitis E outbreaks worldwide. The 7.2 kb genome of the HEV encodes three well-defined open reading frames (ORFs), where the ORF2 translation product acts as the major virion component to form the viral capsid. In recent years, besides forming the capsid, more functions have been revealed for the HEV-ORF2 protein, and it appears that HEV-ORF2 plays multiple functions in both viral replication and pathogenesis. In this review, we systematically summarize the recent research advances regarding the function of the HEV-ORF2 protein such as application in the development of a vaccine, regulation of the innate immune response and cellular signaling, involvement in host tropism and participation in HEV pathogenesis as a novel secretory factor. Progress in understanding more of the function of HEV-ORF2 protein beyond the capsid protein would contribute to improved control and treatment of HEV infection.